Effect of Percentage of Femoral Anterior Cruciate Ligament Insertion Site Reconstructed With Hamstring Tendon on Knee Kinematics and Graft Force. Issue 5 (April 2021) - Sasaki, Yusuke; Fujii, Masataka; Araki, Daisuke; Marshall, Brandon D.; Linde, Monica A.; Smolinski, Patrick; Fu, Freddie H.
Background: Previous studies have stated that closely matching the size of the anterior cruciate ligament (ACL) insertion site footprint is important for biomechanical function and clinical stability after ACL reconstruction. However, the ACL varies widely regarding the area of femoral insertion, tibial insertion, and midsubstance of ACL, and reconstructing the insertion site area with a uniform diameter graft can result in a cross-sectional area that is greater than that of the midsubstance of the native ACL. Therefore, understanding the effect of relative graft size in ACL reconstruction on knee biomechanics is important for surgical planning. Purpose: To assess how the percentage of femoral insertion site affects knee biomechanics in single- and double-bundle ACL reconstruction. Study Design: Controlled laboratory study. Methods: A total of 14 human cadaveric knees were scanned with magnetic resonance imaging and tested using a robotic system under an anterior tibial load and a combined rotational load. In total, 7 knee states were evaluated: intact ACL; deficient ACL; single-bundle ACL reconstruction with approximate graft sizes 25% (small), 50% (medium), and 75% (large) of the femoral insertion site; and double-bundle reconstruction of approximately 50% (medium) and 75% (large) of the femoral insertion site, based on the ratio of the cross-sectional area of the graft to the area of the femoral ACL insertion site determined by magnetic resonance imaging. Results: Anterior tibial translation was not significantly larger than the intact state in single-bundle and double-bundle medium graft reconstructions ( P > .05) and was significantly greater in the single-bundle small graft reconstruction ( P < .05). Anterior knee translation in single-bundle medium graft and large graft reconstructions was not statistically different ( P > .05). In contrast, the anterior tibial translation for double-bundle large graft reconstruction was significantly smaller than for double-bundle medium graft reconstruction at low flexion angles ( P < .05). The single-bundle small graft force was significantly different from the intact ACL in situ force ( P < .05). The graft force with double-bundle large reconstruction was significantly greater than that with the double-bundle medium reconstruction ( P < .05) but was not significantly different from that of the intact ACL ( P > .05). Conclusion: Knee biomechanics with a single-bundle small graft tended to be significantly different from those of the intact knee. In the kinematic and kinetic data for the single- and double-bundle medium graft reconstruction, only the anterior translation at full extension for the single-bundle reconstruction was significantly different (lower) from that of intact knee. This was a time zero study. Clinical Relevance: This study can provide surgeons with guidance in selecting the graft size for ACL reconstruction.